Performance analysis for aerial-towing system. (September 2019) - Khalil, Mostafa
Abstract: The dynamics of open chain systems have been widely investigated as a result of its increased applications such as aerial towing system, submerged towed cable applications, robot manipulators, and bio-mechanical applications. In this study, a practical engineering system, Mine Clearing Line Charge MICLIC system is taken as an example for an open chain system with accelerated end and varying number of segments. To validate the proposed model, a comparison between two different finite segment methods namely Kane's method and Riccati transfer matrix method of linear multibody system (Riccati-MS-TMM) have been performed for a large open chain system. Results show that computational speed of Riccati-MS-TMM outperforms Kane's method due to its huge matrix size to be solved. Then, using a predefined rocket motor total impulse, a parametric study has been performed on MICLIC system to illustrate the impact of different rocket motor thrust profiles on the resulted flight performance including the missile range, flight time, maximum tension applied on the rocket towing bridle, and the missile stability.